Soil permeability and its relation with soil properties in shrimp farming areas - Rekha, P Nila; Jayanthi, M; Muralidhar, M; Gupta, B P; Puthiavan, R (Indian Journal of Fisheries, 2011)
Soil permeability and its relation with soil properties in shrimp farming areas